Characteristics of several varieties of soybean (Glycine max L. Merrill) with giving BAP and GA3 on flooded - lisna dewita lumban gaol; Revandy Iskandar Muda Damanik; Eva Sartini Bayu Girsang (Jurnal Agroekoteknologi, 2018)
This research aim to know the characteristic of some varieties of soybean with giving BAP and GA3 on flooded. The research was conducted at Land Faculty of Agriculture, University of Sumatra Utara, Medan, Indonesia with altitude ± 25 meters in April 2017 until August 2017 using a randomized block design (RAK) with three factors, i. e : varieties (Grobogan, Argomulyo and Demas 1),hormone BAP and GA3 (0 ppm, BAP 30 ppm + GA3 100 ppm, BAP 60 ppm + GA3 200 ppm, and flooding (control and waterlogged. The parameters observed were plant height, leaf number, root volume, number of plants pods, number of seeds of crop, protein totale, chlorophyll totale, and analysis of super oxide dismutase  enzymes. The results showed that varieties significantly affect plant height 2, 3, 5 MST, leaf number 3, 4 MST, root volume, number of plant pods and number of seeds of crop. Hormone treatment significantly affected plant height 2, 3, 4 MST, and root volume. flooding significantly affect chlorophyll analysis.number of plants pods and number of seeds of crop. Interaction varieties and hormone significantly affected plant height 2, 3 MST, leaf number 4 MST and root volume. Interaction varieties and flooding significantly affect root volume. Interaction between varieties, ZPT and flooding significantly affect the root volume.